AB1029 Costs of Biological Agents and Patterns of Biological Therapy in Routine Treatment for Rheumatoid Arthritis. (15th July 2016) - Kamiya, M.; Soen, S.; Kikuchi, H.; Okada, N.
Abstract : Background: Biological agents, introduced in the late 1990s, had significant impact on treatment for rheumatoid arthritis and patient outcomes. However, this treatment is costly, and increases in healthcare payment are of concern. Objectives: This study examined the costs and patterns of biological therapy in routine treatment provided at our hospital. Methods: Subjects were 206 rheumatoid arthritis patients who received etanercept, infliximab, adalimumab, tocilizumab, or abatacept between January 2005 and December 2014. Cumulative costs of each agent administered to a patient over a period of 1, 2, and 3 years were calculated using the current prices of biological agents listed by the National Health Insurance program. Therapy continuation rates and relative dose intensities (RDI) were calculated, and reasons for treatment withdrawal were investigated to ascertain patterns of biological therapy. Results: There were a total of 360 cases of biological agent treatment (174 etanercept cases, 44 infliximab cases, 27 adalimumab cases, 49 tocilizumab cases, and 66 abatacept cases) in 206 rheumatoid arthritis patients, among which 60 etanercept, 9 infliximab, 9 adalimumab, 9 tocilizumab, and 12 abatacept cases were continued for at least 3 years without disruption. When exchanging 1 euro with 127 yen, cumulative costs of one-year and three-year treatment with 25 mg/week etanercept (53 cases) were approximately 6, 160 euro and 17, 490 euro per patient, respectively, while costs with 50 mg/week etanercept (7 cases) were approximately 11, 450 euro and 32, 240 euro per patient, respectively. Costs of 1- and 3-year treatment with infliximab were approximately 11, 910 euro and 32, 430 euro per patient, respectively; those with adalimumab were approximately 13, 450 euro and 38, 590 euro per patient, respectively; those with tocilizumab were approximately 8, 690 euro and 24, 730 euro per patient, respectively; and those with abatacept were approximately 13, 460 euro and 34, 140 euro per patient, respectively. Withdrawal from therapy with any biological agent was due mainly to insufficient therapeutic effect (50% of withdrawals), adverse effects (35.5%), patients' circumstances (9.2%), and remission (5.3%). Therapy continuation rates for etanercept, infliximab, adalimumab, tocilizumab, and abatacept at the end of 3 years were 57.7%, 24.7%, 42%, 25%, and 39.3%, respectively (Kaplan-Meier method). The continuation rate of etanercept therapy was significantly higher than the rates of therapy with any of the other 4 biological agents (log-rank test, P<0.05). Mean RDI values (95% CI) for 3 years were calculated for etanercept 25 mg/week (0.93; 0.81–1.04), etanercept 50 mg/week (0.86; 0.64–1.07), infliximab (1.10; 1.002–1.19), adalimumab (0.95; 0.89–1.01), tocilizumab (0.84; 0.78–0.89), and abatacept (0.85; 0.75–0.94). Decreases in tocilizumab and abatacept dosage were confirmed, and longer dosing intervals were speculated. Furthermore, the dose intensity of infliximab was increased by 10%, indicating increases in dosage and shortened dosing intervals. Significant changes in dosage were not confirmed for etanercept and adalimumab therapy. Conclusions: Etanercept therapy had a high continuation rate. In particular, a 25 mg/week regimen was rarely changed to a 50 mg/week regimen, suggesting that the use of 25 mg/week etanercept therapy may be able to reduce medical costs. Disclosure of Interest: None declared